Peritonitis from perforated sigmoid mass as the first manifestation of metastatic squamous cell lung cancer: a case report and review of literature. Issue 9 (14th September 2020) - Chandra, Raghav; Dogeas, Epameinondas; Nevarez, Nicole; Augustine, Mathew; Huerta, Sergio
Abstract: Lung cancer (LC) is an aggressive malignancy with early metastatic spread and poor prognosis. Gastrointestinal metastases from primary LC are extremely rare with highly variable presentations. In this report, we review the case of a patient who presented with peritonitis secondary to perforated sigmoid mass as the first manifestation of metastatic squamous cell LC.